The effect of dexmedetomidine on inflammatory response of septic rats - Zhang, Jianxing (BMC Anesthesiol, 2015)
BACKGROUND: Some studies have demonstrated dexmedetomidine has anti-inflammatory effect on septic rats. However, the mechanism of how dexmedetomidine exerts these effects is still remained unknown. This study was designed to investigate the mechanism of how dexmedetomidine inhibits the production of inflammatory mediators in cecal ligation and puncturinduced septic rats. METHODS: 48 Sprague-Dawley rats were randomly divided into six groups: sham-operated (sham) group, cecal ligation and puncture (CLP) group, dexmedetomidine 5 μg/kg (DEX5) group, dexmedetomidine 10 μg/kg (DEX10) group,dexmedetomidine + yohimbine (DEX10 + Yoh) group and yohimibine group (Yoh). Blood, bronchoalveolarlavage fluid (BALF) and lung tissues in each group were collected at six hours after dexmedetomidine or yohimbine treatment,. Tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in BALF and plasma were measured by enzyme-linked immunosorbent assay (ELISA). Toll-like receptor-4(TLR4) and myeloid differerntiation factor(MyD88) expression were measuredby quantitative PCR, and extracellular signal-regulated kinase (ERK) 1/2 phosphorylation were determined by western blott. RESULTS: Compared with CLP group, dexmedetomidine significantly decreased not only the production of TNF-α and IL-6 both in plasma and BALF, but also inhibited the expression of TLR4 and MyD88 in mRNA level and the activation of ERK1/2 and NF-κB in the lung tissues of CLP-induced septic rats. All these effects could not be reversed by yohimibine. CONCLUSIONS: Dexmedetomidine treatment can effectively reduce the generation of inflammatory mediators in the plasma and BALF of CLP-induced septic rats. These effects of dexmedetomidine rely on TLR4/MyD88/MAPK/ NF-κB signaling pathway and are independent of α(2)-adrenoceptor.